PENINGKATAN PEMAHAMAN KONSEP BILANGAN MELALUI MEDIA PAPAN FLANEL ANGKA PADA SISWA JENJANG DASAR - Sarwandi Kobandaha; Fatimah Djafar; Miftha Huljannah (LPPM IAD Probolinggo, 2026)
This study aims to examine the use of number flannel board media and its effect on improving understanding of number concepts among Grade I students at SDN 7 Limboto. It employs Classroom Action Research involving 18 students — 10 boys and 8 girls — together with the class teacher, during the academic year 2026. Data were analysed primarily based on the level of learning mastery achieved across successive stages of the research. Findings demonstrate that the number flannel board effectively supported better understanding of number concepts, shown through consistent improvement from pre‑cycle through Cycle I to Cycle II. Before intervention, learning completeness remained low at only 22.22%, meaning just 4 out of 18 students met the Minimum Completeness Criteria (KKM). Following introduction of the media in Cycle I, results rose noticeably to 61.11%, with 11 students achieving mastery. Progress continued into Cycle II, where a more substantial increase brought completeness to 83.33%, representing 15 students who successfully reached the required standard. This upward trend confirms that concrete, visual tools such as the number flannel board are highly suitable and effective for helping early‑grade students grasp basic numerical concepts.